2022
DOI: 10.1007/s42000-022-00380-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic features and clinical course of COVID-19 vaccine–associated subacute thyroiditis

Abstract: Objective This study aimed to identify cases of coronavirus disease 2019 (COVID-19) vaccine-associated subacute thyroiditis (SAT) during the active vaccination period of the pandemic, analyze the characteristics of these cases, and compare them with cases of non-vaccine associated SAT diagnosed in the same period. Methods A total of 55 patients diagnosed with SAT in our outpatient clinic between February and October, 2021, were included in this retrospective single-center study. Results Of the study population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
7
0
4
Order By: Relevance
“…In the current study, 160 SAT cases during the 2-year pandemic period were examined and there was observed to be no increase in the number of newly-diagnosed SAT cases compared to previous years. In the previous study of our clinic, a temporal relationship with the vaccination was observed in 29.1% of SAT cases in the 10-month period following the COVID-19 vaccination in 2021 [16]. The present study showed that there was also no change in the incidence of SAT in the months corresponding to this period (February to October) compared to previous years (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In the current study, 160 SAT cases during the 2-year pandemic period were examined and there was observed to be no increase in the number of newly-diagnosed SAT cases compared to previous years. In the previous study of our clinic, a temporal relationship with the vaccination was observed in 29.1% of SAT cases in the 10-month period following the COVID-19 vaccination in 2021 [16]. The present study showed that there was also no change in the incidence of SAT in the months corresponding to this period (February to October) compared to previous years (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The possible relationship between COVID-19 and SAT became one of the hot topics in the Endocrinology community during the pandemic. Some cases of SAT have been reported following COVID-19 infection and its vaccination, including in our clinic [12][13][14][15][16][17]. The high expression of the angiotensin-converting enzyme-2 (ACE2) receptor used by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to enter the cell in thyroid follicular cells suggests that COVID-19 may directly cause inflammation in thyroid cells [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bostan et al. ( 16 ) retrospectively examined 55 patients diagnosed with SAT, of whom 16 had previously undergone COVID-19 vaccine, with a median of 6.5 days before SAT development. They found no differences concerning the characteristics of vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Crucially, the disease caused by SARS-CoV-2, which was dubbed coronavirus disease 2019 (COVID-19), disproportionately affects persons with preexisting conditions, among them obesity, diabetes, and hypertension, which are endocrine-related disorders [1]. Since the outbreak of the pandemic, Hormones has continued to publish extensively on both COVID-19 and the vaccines developed to help fight the pandemic, as well as on their after-effects, as this issue illustrates [2][3][4]. Our intention is to attract more articles on long COVID while reporting further data concerning possible effects of the vaccines and information on their endocrinecorrelates.…”
mentioning
confidence: 99%